2006
DOI: 10.5713/ajas.2007.200
|View full text |Cite
|
Sign up to set email alerts
|

Low Ruminal pH Reduces Dietary Fiber Digestion via Reduced Microbial Attachment

Abstract: In vitro rumen incubation studies were conducted to determine effects of initial pH on bacterial attachment and fiber digestion. Ruminal fluid pH was adjusted to 5.7, 6.2 and 6.7, and three major fibrolytic bacteria attached to rice straw in the mixed culture were quantified with real-time PCR. The numbers of attached and unattached Fibrobacter succinogenes, Ruminococcus flavefaciens and Ruminocococcus albus were lower (p<0.05) at initial pH of 5.7 without significant difference between those at higher initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 37 publications
8
51
1
4
Order By: Relevance
“…Propionic acid production from dicarboxylic acids (aspartate, malate, fumarate) via the succinate pathway is thermodynamically more efficient than methanogenesis (Offner and Sauvant, 2006). Moreover, rapidly-fermenting diets reduce methane production by decreasing ruminal pH, which affects the growth of methanogens, protozoa (Hook et al, 2011) and cellulolytic bacteria (Sung et al, 2007), and increases passage rate, which reduces protozoans and, thereby, interspecies hydrogen transfer (Kumar et al, 2013). Agle et al (2010) reported that diets with higher proportion of non-structural carbohydrates (52 and 72%) resulted in numerically lower methane emissions (1.5 vs. 3.4 g/hour, respectively), although results showed no difference due to high variability.…”
Section: Starch and Methanogenesismentioning
confidence: 99%
“…Propionic acid production from dicarboxylic acids (aspartate, malate, fumarate) via the succinate pathway is thermodynamically more efficient than methanogenesis (Offner and Sauvant, 2006). Moreover, rapidly-fermenting diets reduce methane production by decreasing ruminal pH, which affects the growth of methanogens, protozoa (Hook et al, 2011) and cellulolytic bacteria (Sung et al, 2007), and increases passage rate, which reduces protozoans and, thereby, interspecies hydrogen transfer (Kumar et al, 2013). Agle et al (2010) reported that diets with higher proportion of non-structural carbohydrates (52 and 72%) resulted in numerically lower methane emissions (1.5 vs. 3.4 g/hour, respectively), although results showed no difference due to high variability.…”
Section: Starch and Methanogenesismentioning
confidence: 99%
“…Erfle et al (1982) menyimpulkan produksi VFA menurun ketika pH rumen turun dari 7 ke 5, karena enzim yang penting untuk memecah serat tidak dapat berfungsi secara efektif pada pH di bawah 6 dan laju pertumbuhan bakteri fibrolitik menurun secara nyata pada pH yang rendah (Russel dan Wilson, 1996). Sung et al (2007) menyatakan bahwa produksi VFA pada pH 6,2 dan 6,8 lebih tinggi dibandingkan pada pH 5,7. Mouriño et al (2001) menyatakan bahwa pH merupakan faktor yang paling penting yang dapat mempengaruhi fermentasi selulosa di dalam rumen dan bakteri selulolitik dapat berkerja optimal pada pH di atas 6.…”
Section: Hasil Dan Pembahasanunclassified
“…These values are in the normal range for the fermentation process. Sung et al (2007) stated that the rumen fluid pH should be maintained more than 6 during fermentation because it is very efficient for microbial growth and fiber digestion in the rumen.…”
Section: Rumen Fermentationmentioning
confidence: 99%